Creativity and Innovation: Keys to Intervene in Learning Contexts - Idoia Fernández Fernández; Ana Eizagirre Sagardia; Maite Arandia Loroño; Pilar Ruiz de Gauna Bahillo; Ainhoa Ezeiza Ramos (Universidad Autónoma de Madrid, 2016)
This paper presents the research study conducted in the Basque Country, as part of a broader European project, denominated Creanova, which team brings together people from different institutions and agencies from eight European countries. Its main aim has been to identify and understand which factors and conditions are required to enhance creative competence and to promote creativity and innovation culture in such diverse fields as Vocational Education and Training (VET), adult education and workplace learning. The general research is structured in two phases: a) Analysis of fifty best practices in six countries (Basque Country, Finland, Ireland, Scotland, Italy and Estonia) and elaboration of a educational model for the analysis and development of creative competences, b) Application of the educational model in four real educational contexts (Basque Country, Finland, Scotland and Italy). The educational model developed has identify four categories (need, interaction, freedom and environment) which bind elements and conditions that stimulate creativity as part of learning. The experimental analysis reveals that: a) The four factors are dimensions that organize the educational practice and they may be considered a tool for designing and analyzing practices that foster creativity, b) They enable the articulation of theory and practice in specific cultural contexts, and c) This model, as a tool, is simple and understandable for those involved in learning processes (formal, non formal and workplace context).